2019
DOI: 10.1002/pmrj.12189
|View full text |Cite
|
Sign up to set email alerts
|

Piriformis Syndrome: A Narrative Review of the Anatomy, Diagnosis, and Treatment

Abstract: Piriformis syndrome is a form of sciatica caused by compression of the sciatic nerve by the piriformis muscle. It is a relatively uncommon, but not insignificant, cause of sciatica. The diagnosis of piriformis syndrome is complicated by the large differential diagnosis of low back and buttock pain with many diagnoses having overlapping symptoms. This narrative review highlights the relevant anatomy, history, physical exam maneuvers, electrodiagnostic findings, and imaging findings that are used to diagnose pir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
64
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 66 publications
1
64
0
3
Order By: Relevance
“…It was observed, that above of this angle, in the hip joint the retroversion of the pelvis occurs caused by ischiofemoral muscles, which may be the source of the pain. It is also known that the flexion in the hip joint is responsible for 44% of changes in the length of the sciactic nerve in the SLR test, whereas, the extension in the knee joint elongates its length by 60mm, contributing to the elongation of the nerve by 49% (21). What is more, the internal rotation and the adduction increase the test sensitivity by additional tension of the nerve structures located at the back of the joints.…”
Section: Biomechanicsmentioning
confidence: 99%
“…It was observed, that above of this angle, in the hip joint the retroversion of the pelvis occurs caused by ischiofemoral muscles, which may be the source of the pain. It is also known that the flexion in the hip joint is responsible for 44% of changes in the length of the sciactic nerve in the SLR test, whereas, the extension in the knee joint elongates its length by 60mm, contributing to the elongation of the nerve by 49% (21). What is more, the internal rotation and the adduction increase the test sensitivity by additional tension of the nerve structures located at the back of the joints.…”
Section: Biomechanicsmentioning
confidence: 99%
“…There is no “gold standard” treatment for PMS; however, first‐line management consists of conservative treatment and lifestyle correction . The main objective of conservative therapies is reducing local pain, muscle tension, and spasm . DN is a therapeutic technique that uses a thin sterile needle to penetrate the skin and affect deep target tissue that is not manually palpable .…”
Section: Introductionmentioning
confidence: 99%
“…The main objective of conservative therapies is reducing local pain, muscle tension, and spasm. 11,12 DN is a therapeutic technique that uses a thin sterile needle to penetrate the skin and affect deep target tissue that is not manually palpable. 13 Although a recent systematic review showed that DN could improve muscle tension, decrease pain, and rapidly increase muscular efficacy, these effects are reported in other muscular conditions, such as myofascial pain syndrome in the neck and lumbar region.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations